KOREKSI MUḤAMMAD ṬĀLIB ATAS TERJEMAH AL-QUR`AN KEMENAG RI: (UJI VALIDITAS) - Ahmad Fuadin; Muhammad Najib (STAI AL-ANWAR SARANG, 2016)
In his Koreksi Terjemah Harfiyah al-Qur`an, Muḥammad Ṭālib, the amÄ«r of the Majelis Mujahidin Indonesia, accuses the official Qur'ânic translation by the Indonesian Ministry of Religion for containing digression and at the same time- supporting radicalism. This article wants to describe and examine Ṭālib's argumentations. It finds that Ṭālib's inappropriate methodology lets him criticize the manuscript over-confidently. First, He has only read it partially and could not catch the whole meaning it provides. Second, Â ignoring the fact that the exegetes whom he was referring to may provide alternatives for one particular word, Ṭālib has uncarefully treated his sources. Key word: Qur'ânic translation, Indonesian Ministry of Religion, Muḥammad Ṭālib, examine validation